Вивчення впливу дії s-гетерил-сукцинатів на мікроклональне розмноження декоративних рослин - Завгородній, М. П.; Дерев'янко, Н. П.; Шкопинська, Т. Є.; Бражко, О. А.; Корнет, М. М.; Генчева, В. І.; Лучкевич, Є. Р.; Шупенюк, В. І.; Zavhorodnii, M. P.; Derevianko, N. P.; Shkopynska, Т. E.; Brazhko, O. A.; et al. (My University, 2024)
Мета роботи. Дослідження впливу нових похідних S-гетерилсукцинатів на мікроклональне розмноження декоративних рослин: клону 112 павловнії повстистої (Paulownia tomentosa (Thunb.) Steud.) і троянди рожевої (Rosa damascena Mill.) сорту Лада; визначення ліпофільності, як одного з важливих факторів, що впливає на прояв біологічної активності. Матеріали і методи. Для синтезованих сполук було проведено in silico скринінг токсичності за допомогою онлайн-сервісів TEST і GUSAR та експериментально досліджено за функціональним станом сперматозоїди чоловіків in vitro. Для виконання окремих етапів розрахунків фізико-хімічних характеристик сполук застосовано АСD-I-Labs. Для оцінки біологічної дії сполук на ризогенез використовували технологію мікроклонального розмноження на живильному середовищі Мураcіге – Скуга. Досліджувані сполуки додавали перед стерилізацією живильного середовища. Контролем слугувало живильне середовище без регуляторів росту. zm311270@gmail.com The aim of the work. Investigation of the impact of new derivatives of S-hetaryl succinates on the microclonal propagation of ornamental plants: clone 112 of Paulownia tomentosa (Thunb.) Steud. and Rosa damascena Mill. 'Lada'; determination of lipophilicity as one of the important factors influencing the manifestation of biological activity. Materials and Methods. For the synthesized compounds, in silico toxicity screening was performed using the online services TEST and GUSAR, and the functional state of male spermatozoa was experimentally studied in vitro. For performing specific stages of calculating the physicochemical characteristics of the compounds, ACD-I-Labs was used. To evaluate the biological effect of the compounds on rhizogenesis, microclonal propagation technology on Murashige-Skoog nutrient medium was employed. The studied compounds were added before the sterilization of the nutrient medium. The control consisted of nutrient medium without growth regulators. Results and Discussion. S-hetaryl succinates, which were previously synthesized via a nucleophilic substitution reaction based on 4-chloroquinolines and 4-chloropyridine and the residue of mercaptosuccinic acid (the structure of the synthesized compounds was confirmed by 1H, 13C NMR spectra), demonstrated a low toxic profile and high growth-stimulating activity in the microclonal propagation of clone 112 of Paulownia tomentosa (Thunb.) Steud. and Rosa damascena Mill. 'Lada'. The studied compounds do not require complex chemical synthesis, are minimally toxic, and stimulate rhizogenesis at low concentrations – 10-⁵ to 10-⁷ mol/L, making them environmentally and economically favorable candidates in the group of growth regulators. The high growth-regulating activity allows them to be recommended for further in-depth study in other plant propagation and cultivation technologies.
Study of the effect of s-heterocyclic succinates on microclonal propagation of ornamental plants
Keywords: S-гетерилсукцинати; регулятори росту; мікроклональне розмноження; синтез; токсичність; ризогенез; S-heterylsuccinates; growth regulators; microclonal propagation; synthesis; toxicity; rhizogenesis